Do Surgical Techniques Used in Groin Lymphadenectomy for Vulval Cancer Affect Morbidity Rates?. Issue 8 (1st November 2011) - Walker, Kate F.; Day, Honor; Abu, Jafaru; Nunns, David; Williamson, Karin; Duncan, Tim
Abstract : Objective: To determine the complication rates associated with differing surgical techniques for groin node dissection for vulval cancer. Materials and Methods: We performed a retrospective case note review of patients undergoing groin node dissection for vulval cancer between 2001 and 2009 at Nottingham University Hospitals NHS Trust. Results: Notes for 56 patients undergoing a total of 98 groin node dissections were examined. Sixty-four percent of the patients had at least one complication from surgery. The use of suction drains was not associated with an increase in complications. However, when drains were used, a short duration of use was associated with high rates of wound breakdown and a long duration of use was associated with higher rates of lymphedema. The use of staples for skin closure was associated with an increased risk of lymphocysts and chronic lymphedema. The greater the number of nodes collected at lymphadenectomy, the higher the risk of lymphocysts and lymphedema. Conclusions: We recommend the use of subcuticular suture for wound closure. Patients who undergo lymphadenectomy with a node count per groin of more than 7 should be closely monitored for lymphedema and referred promptly to specialist services. The prolonged use of suction drainage may increase the risk of lymphedema.